The red-haired woman - Pamuk, Orhan, 1952-; Oklap, Ekin (Haryana, India : Penguin Random House, 2017)
On the outskirts of a town thirty miles from Istanbul a master well digger and his young apprentice are hired to find water on a barren plain. As they struggle in the summer heat, excavating without luck meter by meter, the two will develop a filial bond neither has known before, not the poor middle-aged bachelor nor the middle-class boy whose father disappeared after being arrested for politically subversive activities. The pair will come to depend on each other, and exchange stories reflecting disparate views of the world. But in the nearby town, where they buy provisions and take their evening break, the boy will find an irresistible diversion. The Red Haired woman, an irresistibly alluring member of a travelling theatre company, catches his eye and seems as fascinated by him as he is by her. The young man's wildest dream will be realized, but, when in his distraction, a horrible accident befalls the well-digger, the boy will flee, returning to Istanbul. Only years later will he discover whether he was in fact responsible for his master's death and who the redheaded enchantress was. A beguiling mystery tale of family and romance, of east and west, tradition and modernity --
Donated by Farhana Zahir (Assistant Professor, BBS)
Winner of the Nobel Prize in Literature.
Keywords: Women -- Turkey -- Fiction; Man-woman relationships -- Fiction; Turkish fiction -- Translations into English; Istanbul (Turkey) -- Fiction